On ?-statistical convergence of order ? of sequences of function - Et, Mikail; Cinar, Muhammed; Karakas, Murat (Springeropen, 2013)
In this study we introduce the concept of S-lambda(alpha)(f)-statistical convergence of sequences of real valued functions. Also some relations between S-lambda(alpha)(f)-statistical convergence and strong W-lambda(beta)(f)-summability are given.
Keywords: statistical convergence; sequences of function; Cesaro summability